Simultaneous Papillary Carcinoma in Thyroglossal Duct Cyst and Thyroid - Gustavo Cancela e Penna; Henrique Gomes Mendes; Adele O. Kraft; Cynthia Koeppel Berenstein; Bernardo Fonseca; Wagner José Martorina; Andreise Laurian N. R. de Souza; Gustavo Meyer de Moraes; Kamilla Maria Araújo Brandão Rajão; Bárbara Érika Caldeira Araújo Sousa (Case Reports in Endocrinology)
Thyroglossal duct cyst (TDC) is a cystic expansion of a remnant of the thyroglossal duct tract. Carcinomas in the TDC are extremely rare and are usually an incidental finding after the Sistrunk procedure. In this report, an unusual case of a 36-year-old woman with concurrent papillary thyroid carcinoma arising in the TDC and on the thyroid gland is presented, followed by a discussion of the controversies surrounding the possible origins of a papillary carcinoma in the TDC, as well as the current management options.